2019
DOI: 10.1111/bph.14714
|View full text |Cite|
|
Sign up to set email alerts
|

Tanshinol borneol ester, a novel synthetic small molecule angiogenesis stimulator inspired by botanical formulations for angina pectoris

Abstract: Background and Purpose Tanshinol borneol ester (DBZ) is a novel synthetic compound derived from Dantonic®, a botanical drug approved in 26 countries outside the United States for angina pectoris and currently undergoing FDA Phase III clinical trial. Here, we investigated the angiogenic effects of (S)‐DBZ and (R)‐DBZ isomers in vitro and in vivo. Experimental Approach A network pharmacology approach was used to predict molecular targets of DBZ. The effects of DBZ isomers on proliferation, migration, and tube fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 55 publications
0
27
0
1
Order By: Relevance
“…Dantonic®, a composite Danshen formulation containing standardized extracts of Salviae miltiorrhiza and Panax notoginseng plus borneol, has been broadly used in China for the treatment of myocardial and cerebral ischemic diseases for many decades, and has already completed Phase III clinical trials in the USA (NCT01659580). Inspired by the principle of TCM combinatorial formulations and our previous findings [ [38] , [39] , [40] , [41] , [42] , [43] ], we designed and synthesized tanshinol borneol ester (DBZ, 1,7,7-trimethylbicyclo [2.2.1]heptan-2-yl-3-(3,4-dihydroxyphenyl)-2-hydroxy-propanoate) by chemical combination of tanshinol and borneol (core effective components of Dantonic®) as well as a library of related compounds based on our drug design strategy [ 44 ]. Based on in silico , in vitro and in vivo screenings, DBZ is found to be a safe and a highly pleiotropic molecule endowed with a wide range of beneficial activities, including pro-angiogenic, anti-inflammatory, anti-atherosclerotic and cardiovascular protective effects [ [44] , [45] , [46] , [47] ].…”
Section: Introductionmentioning
confidence: 99%
“…Dantonic®, a composite Danshen formulation containing standardized extracts of Salviae miltiorrhiza and Panax notoginseng plus borneol, has been broadly used in China for the treatment of myocardial and cerebral ischemic diseases for many decades, and has already completed Phase III clinical trials in the USA (NCT01659580). Inspired by the principle of TCM combinatorial formulations and our previous findings [ [38] , [39] , [40] , [41] , [42] , [43] ], we designed and synthesized tanshinol borneol ester (DBZ, 1,7,7-trimethylbicyclo [2.2.1]heptan-2-yl-3-(3,4-dihydroxyphenyl)-2-hydroxy-propanoate) by chemical combination of tanshinol and borneol (core effective components of Dantonic®) as well as a library of related compounds based on our drug design strategy [ 44 ]. Based on in silico , in vitro and in vivo screenings, DBZ is found to be a safe and a highly pleiotropic molecule endowed with a wide range of beneficial activities, including pro-angiogenic, anti-inflammatory, anti-atherosclerotic and cardiovascular protective effects [ [44] , [45] , [46] , [47] ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the angiogenesis-related activities shown in clavukoellians [7], we are committed to find more nardosinane analogues with angiogenesis activity. The anti-and pro-angiogenesis activities of compounds 1-5 were evaluated in a transgenic fluorescent zebrafish (Tg(vegfr2:GFP)) model [12][13][14][15]. Quantitative analysis revealed that compound 5 displayed pro-angiogenesis activity in a PTK787-induced vascular injury zebrafish model at 2.5 μM (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Clavukoellian G (1) and clavukoellian H (2) are the fifth and sixth members of the nitrogen-containing nardosinane sesquiterpenes family so far. Clavukoellian I (3) represents a 6/6/6 tricyclic skeleton with a ∆ 11,12 double bond which is rare in this structure family. Clavukoellian J (4) is a C6-C7 cleavage seco-nardosinane-type sesquiterpene related to clavukoellian E. Clavukoellian K (5) is a new aristolane-type sesquiterpenoid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations